Effects of probiotic, prebiotic and synbiotic intake on blood enzymes and performance of Japanese quails (Coturnix Japonica) - BABAZADEH, D; VAHDATPOUR, T; NIKPIRAN, H; JAFARGHOLIPOUR, M A; VAHDATPOUR, S (The Indian Journal of Animal Sciences, 2011)
The present study was conducted to evaluate the influence of probiotic, prebiotic and synbiotic on performance values and blood enzymes of Japanese Quails. One-day old Japanese quail chicks (192), mean body weight 7.78 g, were randomly assigned in 4 treatments and 4 replicates. The experimental diets consisted of a basal diet without additive (control), 0.2 g/kg probiotic (P), 1.6 g/kg prebiotic (F) and 1.0 g/kg synbiotic (B) added to the basal diet. Birds fed synbiotic showed that a significant elevation in body weight compared to other groups. Feed intake of birds fed synbiotic and prebiotic were higher than control and probiotic fed groups. Birds fed synbiotic exhibited a better feed conversion ratio (3.08) compared to probiotic fed (3.19) and control groups (3.14) (P